2019
DOI: 10.3390/agronomy9070355
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole Promotes Chloride Exclusion and Induces Salt Tolerance in Greenhouse Basil

Abstract: The role of small bioactive molecules (<500 Da) in mechanisms improving resource use efficiency in plants under stress conditions draws increasing interest. One such molecule is omeprazole (OMP), a benzimidazole derivative and inhibitor of animal proton pumps shown to improve nitrate uptake and exclusion of toxic ions, especially of chloride from the cytosol of salt-stressed leaves. Currently, OMP was applied as substrate drench at two rates (0 or 10 μM) on hydroponic basil (Ocimum basilicum L. cv. Genovese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 75 publications
1
19
1
Order By: Relevance
“…This trend was significantly affected by the amount of chlorine. A reduction of the nitrate uptake in leaves was previously reported, also for other leafy greens [26,27]. In this work, while the chorine content in leaves well correlated with its increasing amount in the NS, a large nitrate reduction was present at the highest chlorine concentration.…”
Section: Discussionsupporting
confidence: 83%
“…This trend was significantly affected by the amount of chlorine. A reduction of the nitrate uptake in leaves was previously reported, also for other leafy greens [26,27]. In this work, while the chorine content in leaves well correlated with its increasing amount in the NS, a large nitrate reduction was present at the highest chlorine concentration.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, the mechanisms that control chloride accumulation and partitioning in plants have been scarcely addressed [ 9 ]. When chloride concentration reaches the toxicity threshold, chloroplast membrane stability and Rubisco efficiency are severely affected [ 31 , 32 , 33 ]. Consequently, chloride toxicity in plants induces leaf chlorosis and photosynthesis impairment, which in the most sensitive species causes severe growth and yield loss [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, chloride toxicity in plants induces leaf chlorosis and photosynthesis impairment, which in the most sensitive species causes severe growth and yield loss [ 31 , 33 ]. Several studies have identified chloride exclusion as an important adaptive mechanism for plants to cope with salt stress [ 32 , 33 , 34 ]. Our results show that the commercial cultivar had a higher chlorophyll content ( Figure 1 B), higher CO 2 assimilation rate ( Figure 2 ), higher F v /F m and lower F 0 compared to the landrace ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Duncan’s multiple-range test was used to analyze separated means with a cut-off for statistical significance at p < 0.05. A principal component analysis was employed to investigate how the dominant quanti-qualitative parameters set clustered according to the treatments by using Minitab ® 18 statistical software (Minitab LLC, State College, PA, USA) [ 27 , 65 ]. The percentage increases were calculated as the difference between the treated sample values minus untreated sample values (increase), divided by the untreated sample values and multiplied by 100.…”
Section: Methodsmentioning
confidence: 99%